Code-Switching and Code-Mixing in Digital Content: Language Style used in Zhafira Aqyla's Youtube Video ‘Cerita Anakk Pondok Yang Kuliah S1 di Inggris’ - Avira Malihatunnazihah (Papanda Journal of English Education, 2025)
This research investigates the phenomena of code-switching and code-mixing in digital content, focusing on the language styles used by Zhafira Aqyla in her YouTube video “Cerita Anak Pondok yang Kuliah S1 di Inggris.” The problem addressed is the widespread use of English and Indonesian in daily communication, particularly among youth, without a clear understanding of the types and functions of code-switching and code-mixing. The study aims to identify the types, functions, and dominant forms of these linguistic practices in Zhafira’s content. Employing a descriptive qualitative method, the research utilized the researcher as the main instrument. Data were collected by transcribing and analyzing utterances from one specific YouTube video, with Zhafira Aqyla as the subject, and categorized based on established linguistic theories. The analysis revealed that Zhafira predominantly used insertion as the main type of code-mixing, with 30 occurrences, while tag-switching was the most frequent form of code-switching, followed by inter-sentential and intra-sentential switching. The primary functions identified include clarifying meaning, expressing bilingual identity, maintaining conversational flow, and engaging the audience. The research concludes that code-switching and code-mixing are not only communicative strategies but also stylistic choices that enhance digital content’s relatability and educational value. These findings highlight the importance of multilingual practices in digital media and their potential as effective tools for language learning and audience engagement.